Cost Determinants in Canadian Universities - Dickson, Vaughan (Canadian Journal of Higher Education, 1994)
The relationship between costs per student and enrollment is examined with regression analysis for 61 Canadian universities for the academic year 1986-87. This relationship is explored for overall costs and for sub-components including instruction, library, computing, administration and physical plant costs. Also examined is the influence on cost per student of student mix, student-faculty ratios, faculty wages and research intensity. Among the conclusions are that economies of scale apply to Canadian universities and costs per student are positively related to faculty salaries, faculty research intensity and the proportion of students in graduate programs and scientific disciplines.